1952
DOI: 10.1042/bj0500605
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of phenylacetic acid by Penicillium chrysogenum

Abstract: DEHYDROASCORBIC ACID AND BACTERIA 605 factor is not replaceable by methylene blue, pyocyanine, glutathione, coenzyme ii, yeast extract, or boiled or unboiled whole yeast. 3. The effect of hydrogen-donator concentration on the rate of DHA reduction, as compared with the rate of methylene-blue reduction, indicates that the rate of hydrogen transfer may be greatly reduced in the DHA-reducing system. 4. Growth on lactate or formate in place of glucose increases the hydrogenase activity, but decreases the DHA-reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1955
1955
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 3 publications
(1 reference statement)
1
8
0
Order By: Relevance
“…Industrial penicillin production by Penicillium chrysogenum strains requires the addition of PhAc, which is the side-chain precursor for the synthesis of penicillin G. Part of the added PhAc is oxidized (26), and it is not transformed into penicillin. Therefore, strain improvement programs using mutation and selection techniques have been directed to prevent such oxidation (27).…”
Section: Discussionmentioning
confidence: 99%
“…Industrial penicillin production by Penicillium chrysogenum strains requires the addition of PhAc, which is the side-chain precursor for the synthesis of penicillin G. Part of the added PhAc is oxidized (26), and it is not transformed into penicillin. Therefore, strain improvement programs using mutation and selection techniques have been directed to prevent such oxidation (27).…”
Section: Discussionmentioning
confidence: 99%
“…Octopamine, an invertebrate neurotransmitter also found in mammalian brain, is metabolised to 4-hydroxy- mandelate which is excreted [45]. L-Phenylalanine, phenylacetate and L-tyrosine are converted into mandelate and 4-hydroxymandelate by a wide range of organisms including Polyporus hispidus [46], Penicillium chrysogenum [47], Aspergillus niger [48], phytoplankton [49] and red algae [50], although some of the enzymes thought to be involved in the postulated metabolic pathways ( Fig. 5) have not been identified and in particular the mechanism whereby the a-carbon of phenylacetate (or 4-hydroxyphenylacetate) is hydroxylated to give mandelate (or 4-hydroxymandelate) is not known.…”
Section: Mandelate and Related Com-pounds In Naturementioning
confidence: 99%
“…[104] and Flavobacterium sp. [105]; c, Penicillium chrysogenum [47], mechanism uncertain, see Section 3; d, Pseudomonas putida [77], Lactobacillus sp. [106], Bacillus sp.…”
Section: Degradation Of Ring-substituted Mandelatesmentioning
confidence: 99%
“…A greater variety of pathways have been described for fungi. The oxidation of phenylacetic acid by Penicillium chrysogenum proceeded through mandelic acid to benzaldehyde (HOCKENHULL et al 1952), while a strain of Aspergillus niger 256 BROWN and SWINBURNE produced protocatechuic acid, the pathway involving the formation of 3-hydroxyphenylacetic acid and 3-hydroxybenzyl alcohol (SUGUMARAN et al 1972). BOCKS (1967), however, showed that the Mulder strain of A. niger metabolized phenylacetic acid to 2-, 3-and 4-hydroxyphenylacetic acids and 2,5-dihydroxyphenylacetic acid (homogentisic acid).…”
Section: Resultsmentioning
confidence: 99%